2011
DOI: 10.1073/pnas.1101657108
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-responsive candidate cell of origin for diffuse intrinsic pontine glioma

Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are highly aggressive tumors of childhood that are almost universally fatal. Our understanding of this devastating cancer is limited by a dearth of available tissue for study and by the lack of a faithful animal model. Intriguingly, DIPGs are restricted to the ventral pons and occur during a narrow window of middle childhood, suggesting dysregulation of a postnatal neurodevelopmental process. Here, we report the identification of a previously undescribed population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
300
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 279 publications
(333 citation statements)
references
References 34 publications
25
300
0
Order By: Relevance
“…Of these genes, Pax3, Irx5, and Chl1 were also differentially regulated between the Olig2-compartments of BSG and CG suggesting that they represent biological differences within the tumor cells. As Olig2 characterizes the majority of human BSG, particularly the oligodendroglial (PDGFRA) and H3-K27M subgroups [5,8,50,51], as well as marks a candidate cell-of-origin for BSG [52], the expression profile of these cells has important implications for at least a subset of the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of these genes, Pax3, Irx5, and Chl1 were also differentially regulated between the Olig2-compartments of BSG and CG suggesting that they represent biological differences within the tumor cells. As Olig2 characterizes the majority of human BSG, particularly the oligodendroglial (PDGFRA) and H3-K27M subgroups [5,8,50,51], as well as marks a candidate cell-of-origin for BSG [52], the expression profile of these cells has important implications for at least a subset of the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was supported by the fact that these mutations were not found in exome-sequencing data from adult gliomas [16]. Another group suggested that the Hedgehog signaling pathway, which is highly active in DIPG, could be involved in the origin of DIPG [17]. They observed that unregulated activity of the Hedgehog pathway resulted in hypertrophy of the healthy pons of mice [17].…”
Section: Editorialmentioning
confidence: 94%
“…Another group suggested that the Hedgehog signaling pathway, which is highly active in DIPG, could be involved in the origin of DIPG [17]. They observed that unregulated activity of the Hedgehog pathway resulted in hypertrophy of the healthy pons of mice [17]. All these exciting new biological insights and discoveries of multiple pathways are helping to increase the understanding of DIPG and developing new multi-targeted therapy approaches for this disease.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations